KONSEP UMMAH WAHIDAH DALAM AL-QUR’AN: Kajian Atas Tafsir Al-Maraghi - Putri, Poppy Devinna; Dahliana, Yeti (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
Allah created humans as a ummah wahidah, even though humanity consists of various tribes and races humanity is one people, but recently humans often clash with each other, and even fellow Muslims have become divided. others are caused by differences of opinion that give rise to disputes. Even though Islam commands its people to unite with each other, not divide and not fight because Islam exists to be able to care for existing differences, this is proven by the existence of nine verses that discuss the unity and unity of the Ummah. Therefore, the researcher wants to examine more deeply the concept of ummah wahidah in the thoughts of Muhammad Mustafa al-Maraghi in the book Tafsir al-Maraghi. This research aims to find out the meaning of the phrase ummah wahidah in al-Maraghi's interpretation, find out the relevance of the concept of ummah wahidah offered in the current context, and answer existing problems. The method used in this research is library research. The results of this research are the results of Sheikh al-Maraghi's interpretation of nine verses containing several phrases ummah wahidah. The meanings in Sheikh al-Maraghi's interpretation include one person in terms of religion, one person in terms of their faith, one person in terms of the Shari'a, one person in terms of disbelief, and one person in the search for truth. The concept of ummah wahidah offered by Sheikh al-Maraghi is still relevant in the current context, seen from the fact that currently there are still many conflicts between communities caused by differences in views. So this interpretation is useful as a solution to existing problems. Pada dasarnya manusia Allah ciptakan sebagai ummah wahidah, meskipun umat manusia terdiri dari berbagai macam suku, ras yang berbeda-beda. Belakangan ini umat manusia saling berselisih bahkan sesama umat Islam pun berbepecah belah, salah satunya, disebabkan oleh perbedaan pendapat. Padahal Islam memerintahkan umatnya untuk saling bersatu, tidak berpecah belah dan tidak berselisih karena Islam hadir untuk bisa merawat perbedaan yang ada. Hal ini dibuktikan dengan adanya sembilan ayat yang membahas mengenai persatuan dan kesatuan umat. Oleh karena itu, peneliti ingin mengkaji lebih dalam mengenai konsep ummah wahidah dalam pemikiran Muhammad Mustafa al-Maraghi dalam kitab tafsir al-Maraghi. Penelitian ini bertujuan untuk mengetahui makna dari lafal ummah wahidah dalam tafsir al-Maraghi, mengetahui relevansi konsep ummah wahidah yang ditawarkan dengan konteks masa kini dan  menjawab problem yang ada. Metode yang digunakan dalam penelitian ini adalah penelitian “library research” (kepustakaan). Hasil dari penelitian ini adalah dari hasil penafsiran Syeikh al-Maraghi pada sembilan ayat yang mengandung lafal ummah wahidah, terdapat beberapa makna di antaranya, umat yang satu dalam hal agama, umat yang satu dalam hal keimanan, umat yang satu dalam hal syariat, umat yang satu dalam hal kekufuran, dan umat yang satu dalam mencari kebenaran. Konsep ummah wahidah yang dtiwarkan oleh Syeikh al-Maraghi masih relevan dengan konteks masa kini, dilihat dari  di masa sekarang masih banyak konflik perpecahan antar umat yang disebabkan oleh perbedaan pandangan. Sehingga, penafsiran ini berguna untuk menjadi solusi permasalahan yang ada.